2020
DOI: 10.1128/mbio.02146-20
|View full text |Cite|
|
Sign up to set email alerts
|

Bacteria Contribute to Plant Secondary Compound Degradation in a Generalist Herbivore System

Abstract: Herbivores must overcome a variety of plant defenses, including coping with plant secondary compounds (PSCs). To help detoxify these defensive chemicals, several insect herbivores are known to harbor gut microbiota with the metabolic capacity to degrade PSCs. Leaf-cutter ants are generalist herbivores, obtaining sustenance from specialized fungus gardens that act as external digestive systems and which degrade the diverse collection of plants foraged by the ants. There is in vitro evidence that certain PSCs ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…Our study enabled us to detect molecular families and chemical transformations occurring in a fungus garden. These results will enable further investigations concerning the roles of these metabolites, as has been recently demonstrated for fatty acids in fungus gardens ( 24 ) and for plant volatile compounds that are modified by fungus garden-associated bacteria ( 26 ). Because previous reports have shown that the enzymes produced in the fungus garden vary depending on the available substrates ( 53 ), we expect that the chemical modifications and the types of transformations observed in this study will also vary based on changes in the substrates available for the colony.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Our study enabled us to detect molecular families and chemical transformations occurring in a fungus garden. These results will enable further investigations concerning the roles of these metabolites, as has been recently demonstrated for fatty acids in fungus gardens ( 24 ) and for plant volatile compounds that are modified by fungus garden-associated bacteria ( 26 ). Because previous reports have shown that the enzymes produced in the fungus garden vary depending on the available substrates ( 53 ), we expect that the chemical modifications and the types of transformations observed in this study will also vary based on changes in the substrates available for the colony.…”
Section: Resultsmentioning
confidence: 70%
“…Because previous reports have shown that the enzymes produced in the fungus garden vary depending on the available substrates ( 53 ), we expect that the chemical modifications and the types of transformations observed in this study will also vary based on changes in the substrates available for the colony. Additionally, environmental factors such as temperature or humidity and the composition of microbiomes that are associated with ants and their fungus gardens ( 26 ) will likely also influence these modifications in natural ecosystems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that we would see an enrichment for plant defense compound detoxification genes in the top of the fungus garden, where fresh plant material is deposited. To elucidate the role of bacteria in plant defense compound remediation, closely controlled experiments with particular defense compounds of interest applied to bacterial cultures and to fungus gardens would be necessary, and have been pursued as a follow-up to this study (Francoeur et al, 2020). Pinto-Tomás et al (2009) established that Pantoea and Klebsiella bacteria in Central American leaf-cutter ant fungus gardens supplement the ant diet through nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Insect gut is the house of diverse microbiomes, which are evolving to play important roles in insect physiology and ecology, supporting growth, development, and survival of their hosts [ 22 , 23 , 24 ]. In general, gut microbiota can contribute to the nutrition provision for host [ 25 ], host immunity [ 26 ], host behavior [ 27 ], and mediate detoxification of plant secondary compounds [ 28 , 29 ] and insecticides [ 30 ]. Conversely, multiple factors such as host, environment, and diet can shape the structure of gut microbial communities [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%